ChemInform Abstract: Oxygen Incorporation into Infinite‐Layer Structure AFeO2 (A: Sr or Ca). Issue 30 (29th July 2014) - Matsumoto, Kazuya; Kan, Daisuke; Ichikawa, Noriya; Hosokawa, Saburo; Kageyama, Hiroshi; Shimakawa, Yuichi
Abstract Oxygen incorporation into the title compounds is investigated by XRD and thermogravimetry.